2015
DOI: 10.1097/md.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Early Percutaneous Cholecystostomy in Severe Acute Cholecystitis Reduces the Complication Rate and Duration of Hospital Stay

Abstract: Supplemental digital content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
3
42
0
4
Order By: Relevance
“…However, our multivariate analysis showed that not old age, but a higher serum Cr level on admission (≥2.0 mg/dL) was the only independent predictor for the in‐hospital mortality. Consistent with the present findings, a study from Taiwan also showed that a higher serum Cr level (≥1.5 mg/dL) was an independent risk factor for in‐hospital mortality in patients with severe AC undergoing percutaneous drainage . A recent report from Italy showed that end‐stage renal disease was an independent risk factor for complex laparoscopic cholecystectomy, defined as gallbladder wall rupture and/or bleeding .…”
Section: Discussionsupporting
confidence: 90%
“…However, our multivariate analysis showed that not old age, but a higher serum Cr level on admission (≥2.0 mg/dL) was the only independent predictor for the in‐hospital mortality. Consistent with the present findings, a study from Taiwan also showed that a higher serum Cr level (≥1.5 mg/dL) was an independent risk factor for in‐hospital mortality in patients with severe AC undergoing percutaneous drainage . A recent report from Italy showed that end‐stage renal disease was an independent risk factor for complex laparoscopic cholecystectomy, defined as gallbladder wall rupture and/or bleeding .…”
Section: Discussionsupporting
confidence: 90%
“…5,6 For patients not fit for surgery, delayed percutaneous cholecystostomy drainage of more than 24 hours is associated with increased morbidity and length of hospital stay (LOS). 7 However there remains uncertainty regarding optimal timing of cholecystectomy or cholecystostomy drainage in hospitalized patients with acute cholecystitis, especially in the critically ill population. This situation presents therapeutic challenges, as not all hospitals have access to interventional radiology and acute care surgery.…”
mentioning
confidence: 99%
“…Therefore, the parameters discussed above affected hospitalization duration and cost-effectivity. A study by Chou et al [10] and Kapan et al [27] indicated that patients who underwent PC had decreased hospitalization duration. In this study, we also investigated the postoperative hospitalization duration between the groups and found that patients who underwent PC plus cholecystectomy had shorter hospitalization duration than those who underwent cholecystectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] PC is being preferred as a bridge treatment before cholecystectomy or a definitive non-surgical treatment method for AC in elderly patients. [2,[10][11][12] In the…”
mentioning
confidence: 99%